A szülői felügyeleti jog megszüntetésének hatályos jogi szabályozása a Polgári Törvénykönyvben - Csizmadiáné Pethő, Tímea (Debreceni Jogi Műhely, 2017)
Being a judge practicing on the area of the law of crimes I rarely come across with the need to apply civil law. Nevertheless, a handful legal concepts may be applied also by criminal courts. One of these concepts is the termination of parental control. Before turning to relevant case analysis in my study, I focus on the principle of the "child's best interest" which is referred to under article 3 of the New York Convention on the rights of children and which has a general fundamental applicability in respect of all provisions of the Convention. This principle must apply not only in civil, but also in criminal proceedings and generally in all types of proceedings irrespective of the area of law such proceedings fall under. Special emphasis is attributed to the legal consequences of terminating parental control and to the distinction of cases where the termination of parental control by the court is mandatory and where such a decision is made in the discretion of the court. I pay separate attention to cases where the court has convicted the parent of a crime committed wilfully against the convicted person's own child and in which cases the convicted person is sentenced to prisonment and as a result of these the criminal court has competence to order the termination of parental control. I address also some issues relating to matters of proof and evidence in connection with crimes of domestic violence. Finally, I explain the nature of a child-focused jurisdiction through the presentation of the Hungarian system which ensures to respect and to give effect to the rights of children to the maximum extent possible. The ability of providing special treatment for children in court proceedings is of the utmost importance.